Change management at clusters: first results of a change management survey among clusters at European level - Völgyiné Nadabán, Márta (Acta Agraria Debreceniensis, 2013)
Change is a natural characteristic of organisations at the end of the twentieth century and in the upcoming ages. The dynamism of the environmental effects and the heterogeneity of the environment urge organisations to continuously adapt to these changes. It means that organisations and clusters which are more or less agglomeration of organizations should be open to external influences and those organisations responding faster are more viable. From the professional literature several change management methods and tools are known. However, few sources deal with clusters. A cluster is also a unique organizational structure: its specialty lies in the fact that even large clusters are built up from smaller organisations in an environment where flexibility, rapid economic decisions and high level buoyancy is needed. The question is whether the general change management methods and approaches can be interpreted regarding clusters.